Geographical variation in cone traits of Pinus nigra as result of crossbill predation: implications for assisted migration. (26th December 2018) - Tíscar, Pedro Antonio
Abstract: The interaction between Spanish Black pine ( Pinus nigra subsp. salzmannii ) and common crossbill ( Loxia curvirostra ) could have resulted in a geographic mosaic of coevolution in the Iberian Peninsula. In turn, this coevolutionary interaction might limit the future applicability of assisted migration as a tool to adapt forests of Spanish Black pine to ongoing climate change. Several cone and seed traits were measured in 740 cones collected at six stands distributed across the range of Spanish Black pine. Data were analysed by means of linear-mixed effects models, canonical analysis of principal coordinates and random-forest analysis. Results showed that cones from the northern pine populations exhibited more defensive traits against crossbill predation than cones from the central and southern populations, resulting in a geographic mosaic of selection. Assisted migration of P. nigra would involve moving southern populations toward the north of the species' range and would result in introducing the genotypes of pines with poorly defended cones into areas where crossbills are comparatively more abundant. The resulting risks for the regeneration prospects of the translocated trees are discussed.